Effects of caloric and noncaloric sweeteners on antroduodenal motility, gastrointestinal hormone secretion and appetite-related sensations in healthy subjects. Issue 5 (20th April 2018) - Meyer-Gerspach, Anne Christin; Biesiekierski, Jessica R; Deloose, Eveline; Clevers, Egbert; Rotondo, Alessandra; Rehfeld, Jens F; Depoortere, Inge; Van Oudenhove, Lukas; Tack, Jan
ABSTRACT: Background: Activation of gastrointestinal (GI) sweet taste receptors by caloric sweeteners triggers secretion of anorexigenic and inhibition of orexigenic GI hormones to regulate food intake. The effect of noncaloric sweeteners on these mechanisms is controversial. We have recently shown that motilin-induced gastric phase III contractions signal hunger feelings, thereby identifying GI motility, and its regulatory hormone motilin, as novel players in food intake regulation. Objective: The objective of the present study was to determine the effect of caloric and noncaloric sweeteners on GI motility, GI hormone secretion, and hunger in humans. Design: The study was a randomized, double-blind, crossover trial. Twelve healthy volunteers underwent 4 gastroduodenal manometry recordings in which the occurrence of phase III contractions was followed by the intragastric (i.g.) administration of 250 mL tap water or equisweet caloric ( 1 ) 50 g glucose and 2 ) 25 g fructose) and noncaloric sweeteners [220 mg acesulfame-K (ace-K)] dissolved in 250 mL tap water. Measurement continued until ≥1 subsequent phase III. Blood samples were collected for the measurement of GI hormones. Visual analog scales were used to rate hunger and satiety feelings. Response curves were analyzed using (generalized) linear mixed models. Results: We found: 1 ) an inhibitory effect of the 2 caloric sweeteners on antral motility ( P  < 0.01), but no effect after ace-K, 2 ) an inhibitory effect of the 2 caloric sweeteners on motilin secretion ( P  < 0.01), but no effect after ace-K, 3 ) an early increase in cholecystokinin (CCK) secretion after the 2 caloric sweeteners ( P  < 0.01), but no effect after ace-K, and 4 ) an initial stronger decrease in hunger feelings and stronger increase in satiety after ace-K ( P  < 0.05), followed by a steeper return of hunger and decrease of satiety after ace-K ( P  < 0.05). Conclusions: Our results demonstrate, for the first time to our knowledge, that the caloric sweeteners glucose and fructose, but not the noncaloric sweetener ace-K, inhibit motilin secretion and antral motility while increasing CCK secretion. This trial was registered at clinicaltrials.gov as NCT02891525.